A rare manifestation of adrenocortical carcinoma as a mimic of pheochromocytoma: a case report and literature review - Sobolewska, Joanna; Respondek, Wioleta; Witek, Przemyslaw (Frontiers in Endocrinology, 2025)
The primary management in the care of patients with adrenal incidentalomas is to determine the oncologic risk, namely, the possibility of malignancy. The first place among adrenal incidentaloma lesions requiring diagnosis and treatment promptly is adrenocortical carcinoma (ACC). Similarly, in the case of pheochromocytoma, the lack of early diagnosis worsens the patient’s prognosis. Even though both ACC and pheochromocytoma are among the less frequent adrenal lesions, neither should be excluded during differential diagnostics, especially in patients with an equivocal clinical presentation and non-typical adenoma radiological features. ACC presenting as pheochromocytoma is one of the few cases described in the literature, some of which could not collect exhaustive clinical data. Herein, in this article, we would like to provide an overview of reported ACC cases clinically manifesting as pheochromocytoma, based on the clinical image of a 59-year-old female patient with unintentional weight loss, non-specific abdominal pain, a diagnosis of hypertension, and significantly elevated excretion of 3-methoxytyramine in a 24-h urine collection, histopathologically diagnosed with ACC. The case presented emphasizes how crucial a comprehensive diagnostics and individual approach to the patient would be.